Agri-food Systems Innovation: Pathways to Impact - CSIRO; CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2016)
The CSIRO Agriculture and Food & the CGIAR Independent Science and Partnership Council (ISPC) Secretariat are collaborating to explore the nature of agri-food systems innovation and impact. This workshop report is a record of the key outcomes from a workshop held on the 14-15 December 2016 in Canberra, Australia.